A proposal for revising the Kulturindustrie of Adorno and Horkheimer from the praxeology of Austrian philosopher Ludwig von Mises - Rafael Ribeiro Santos (Revista da Tulha)
A proposal for revising the Kultureindustrie of Adorno and Horkheimer from the praxeology of the Austrian philosopher Ludwig von Mises. The term Kultureindustrie of Theodor Adorno and Max Horkheimer is a pessimistic reading about serial manufacturing procedures that artistic and cultural production has been submitted after the Industrial Revolution. The production and marketing standards and the regulation of professions, al under state control, it implies, according to Mises, in favor of initiatives that represent the interests of politicians, not the people. Free initiative in educational, cultural and artistic segments thus is prevented or hindered from operating outside the interests of those in power. But the artistic activity is individualistic, and is necessary freedom to negotiate and, in poetics, liberty of expression.